CRISPR in mobile genetic elements: counter-defense, inter-element competition and RNA-guided transposition - Eugene V. Koonin; Kira S. Makarova (BMC Biology, 2024)
Abstract CRISPR are adaptive immunity systems that protect bacteria and archaea from viruses and other mobile genetic elements (MGE) via an RNA-guided interference mechanism. However, in the course of the host-parasite co-evolution, CRISPR systems have been recruited by MGE themselves for counter-defense or other functions. Some bacteriophages encode fully functional CRISPR systems that target host defense systems, and many others recruited individual components of CRISPR systems, such as single repeat units that inhibit host CRISPR systems and CRISPR mini-arrays that target related viruses contributing to inter-virus competition. Many plasmids carry type IV or subtype V-M CRISPR systems that appear to be involved in inter-plasmid competition. Numerous Tn7-like and Mu-like transposons encode CRISPR-associated transposases (CASTs) in which interference-defective CRISPR systems of type I or type V mediate RNA-guided, site-specific transposition. The recruitment of CRISPR systems and their components by MGE is a manifestation of extensive gene shuttling between host immune systems and MGE, a major trend in the coevolution of MGE with their hosts.